Improving task management in the Cash and Custodial Division - Masa, Kaila-Trish (Animo Repository, 2022)
This action research aimed to address the weak task management of the Cash and Custodial Division. Through the collaborative discussions of our team, we were able to identify the need for a task monitoring tool in order to properly manage our tasks. As part of a government institution, we have utilized the Customer-Oriented Service Enhancement System (COSES) model to aid us in determining areas of improvements in our unit and in enhancing our service delivery to clients. Furthermore, we have utilized the Kanban Method in the conceptualization and creation of our task monitoring tool. The conduct of our first cycle focused on creating and establishing our task monitoring tool. In discussing the platform to be used, the collaborators agreed to employ Google Sheets given that the existing document monitoring also employs the same. In our second cycle, we focused on incorporating our task monitoring tool in the day-to-day operations of the Cash and Custodial Division. To ensure continuous use of the task monitoring tool, the team decided to update our process flow to include task monitoring in our transaction processing. Guided by Kurt Lewin’s change management model, we were able to transition and implement our desired changes throughout the action research cycles.